Decomposition of bioacustic signals using families of orthogonal polynomials (Revista de Investigaciones Universidad del Quindío, 2015)
This study presents a decomposition technique of Bio-acoustic signals using two families of orthogonal polynomials as basis functions. This technique is oriented to be implemented in low computing capability devices such as wireless sensor networks. Therefore, this technique should be quick and effi cient and should allow high compression of information and a good quality in its reconstruction. In this article the foundation of decomposition using orthogonal polynomials families is explained. The procedure used is to achieve adequate resolution, which allows greater information compression and better quality in the reconstruction of the signal. Finally, the results obtained by applying the method to functions generated artifi cially and to sound recordings at Chingaza moor will be (Cundinamarca) exposed. Those sound recordings were provided by the Alexander von Humboldt Institute. The results are compared with the traditional Fourier Transform.
Keywords: Orthogonal polynomials; decomposition of Signals; Bioacoustic signals; quality reconstruction